Nodular Episclerokeratitis in Dogs - Araújo Sonego, Dábila; Pinto Ribeiro , Alexandre; Lima de Andrade , Alexandre; Tiemi Tuboni , Lais (Acta Scientiae Veterinariae, 2022)
Background: Episcleral inflammation may be assumed to be primary immune-mediated, secondary to intra-or extraocular diseases, or systemic abnormalities. We aimed to report a confirmed and another suspect case of nodular episclerokeratites (NEK) due to its rarity in the clinical setting and the paucity of case reports in Brazilian literature. Cases: Case 1. Refers to a 7-year-old castrated male, Collie-mixed breed, presenting with epiphora and an irregular ocular surface shape in the left eye (LE). Ophthalmic evaluation of this eye revealed mucoid discharge, conjunctival hyperemia, episcleral injection, and a gelatinous mass in the temporal limbic region. Biomicroscopic evaluation of the anterior chamber, lens, and vitreous was impaired in the LE because of corneal vessels and a mild flare in the aqueous humor. Histopathology of a scleral biopsy revealed the presence of lymphocytes, histiocytes, and some plasma cells. Positive CD3-lymphocytes were observed by immunohistochemistry, confirming the diagnosis of NEK. Case 2. Refers to a 8-year-old, spayed female Border Collie with a history of exophthalmos, conjunctival hyperemia, and inability to close the eyelid of the LE. During ophthalmic examination, an irregular espicleral nodule of approximately 9 mm was also found in the temporal limbic region, along with enlargement of episcleral vessels and scleral thinning at the equatorial region. The cornea showed mild and diffuse edema, and white crystal-like deposits were distributed in a band-like fashion at the dorsal aspect. Ultrasonography revealed scleral thinning without evidence of a mass effect arising from the iris, ciliary body, or retrobulbar space. Based on these findings, NEK was suspected. In both cases, the clinical signs reduced significantly after seven days of topical treatment with corticosteroids and cyclosporine. Discussion: It is assumed that scleral disorders are primarily immune mediated. However, such conditions may develop secondary to ocular trauma (surgery and foreign bodies), Ehrlichia canis, and Onchocerca spp. Infections and situations were ruled out in both cases. In case 1, additional histological and immunohistochemical findings supported a primary and immune-mediated scleral disease. Although the definitive diagnosis was not confirmed by histology in case 2, one can assume that the episcleral inflammation may have arisen due to an immune-mediated disorder once the eye responded positively to corticosteroid therapy. Additionally, secondary glaucoma was excluded as a possible diagnosis in case 2, because the intraocular pressure of the affected eye was below the reference range for dogs, coupled with the irregular appearance of the episclera, which is not characteristic of canine glaucoma. However, in case 2, because remission of the masses of neoplastic origin after corticotherapy was not expected, the tumor was discarded. NEK has a characteristic ploriferative behavior and resistance to topical immunosuppression; clinical recurrence was not observed in the LE of either patient who remained on treatment after 60 days of follow-up. Regarding prognosis, one study showed a correlation between cellular contingent and therapeutic responses. The percentage of positive CD79a cells (B-lymphocytes) was significantly higher in cases of epicleritis and NEK, in which a poor response was achieved after topical immunosuppressive treatment. As shown by the veterinary literature and the cases described here, the complete remission of NEK is more common in unilateral cases, as confirmed after a 12-month follow-up. The 2 reported cases are useful for clarifying the common findings, diagnosis, and long-term management of NEK. Scleral abnormalities, such as NEK, must be included in the list of differential diagnoses of glaucoma, neoplasia, and endophthalmitis during medical examination. Keywords: keratitis, uveitis, neoplasia, immunosuppression, dog. Título: Episcleroceratite nodular granulomatosa em cães Descritores: ceratite, uveíte, neoplasia, imunossupressão, cão.